Participatory Slum Upgrading and Urban Peacebuilding Challenges in Favela Settlements: The Vila Viva Program at Aglomerado da Serra (Belo Horizonte, Brazil) - Claudio Beato; César Velásquez (Journal of Illicit Economies and Development, 2021)
The concentration of urban violence in certain settlements in Latin America and the possibility of expansion have been latent concerns in slum upgrading. This intervention is potentially an urban peace strategy, especially when it is open to local participation and the promotion of capacities for collective action. However, the political economy behind upgrading shows that these are settings of competence for power and resources. Different factors (e.g., heterogeneity and population size, and project design) account for the bias towards a local elite, which is functional to the interests of public authorities. But, in contexts where power is fluid and challengeable, the informal arrangements between actors involved are more important as mediating social mechanisms of the peacebuilding efforts in the upgrading intervention and their outcomes. This article focuses on the Vila Viva slum-upgrading experience in Aglomerado da Serra, starting in 2005 in Belo Horizonte (Brazil). Social Network Analysis (SNA) models were applied to study the ties linking activists with public and private community initiatives. Interviews and a sociometric survey were used to collect information. The analysed social mechanisms (closure and brokerage types) depicted interaction frameworks with public authorities of two profiles of community activists: traditional and emerging. The first one was functional to the situational crime control approach of Vila Viva, in contrast with territorial rooting defended by emerging activists. The Vila Viva program upgraded the area’s connectivity with the city and broadened the market share of the favela´s drug dealers. After which, they assumed situational control to protect external buyers.